Pengaruh Visual Konten dan Komunikasi Persuasif Influencer Instagram @sashfir Terhadap Keputusan Pembelian Produk Fashion di Kalangan Mahasiswa Universitas Negeri di Kota Surakarta - Salvira Nur Fatika; Andrine Prima Afneta Azril (Universitas Sebelas Maret (UNS), 2026)
Instagram has become one of the most influential digital platforms for persuasive communication, particularly in shaping consumer behavior in the fashion industry. This study is grounded in the Elaboration Likelihood Model (ELM), which explains how individuals process persuasive messages through either the central route or peripheral route depending on their level of involvement. This research employed a descriptive quantitative approach using an online questionnaire distributed to 100 respondents who are followers of the Instagram account @sashfir. The variables examined include visual content and persuasive communication as predictors of purchase decisions. The results show that both visual content and persuasive communication have a significant influence on purchase decisions, with visual content exhibiting a negative coefficient and persuasive communication showing a positive effect. This indicates that while the visual presentation of fashion products may not always resonate strongly, followers still consider the information, credibility, and message delivery of the influencer when evaluating purchasing decisions. Simultaneously, both variables are proven to significantly influence consumer purchase decisions. These findings emphasize the importance of strengthening message relevance, enhancing visual consistency, and improving influencer credibility in digital fashion marketing strategies.